In vitro anti-cancer and antimicrobial activities of Abelmoschus esculentus root extracts - Desai, Akash; Yakub, Manure Md. Javeed Md.; Karade, Priti; Patil, Sudhir S. (Bangladesh Journal of Pharmacology, 2025)
This study explored the potential of Abelmoschus esculentus for treating oral squamous cell carcinoma and associated risk factors. The extract, obtained via soxhlet extraction, was formulated into a carbopol 940 gel for topical and oral mucosal delivery. Phytochemical screening revealed alkaloids, flavonoids, carbohydrates, and phenolic compounds. The Folin-Ciocalteu method showed high total phenolic content (R²=0.9953). The extract exhibited promising in vitro anti-cancer activity against a squamous cell carcinoma cell line, achieving a 52.9% inhibition rate at the highest concentration 100 µg/mL. Additionally, the extract demonstrated potential antibacterial activity against Helicobacter pylori ATCC 43501 compared to clarithromycin. The extract-loaded gel formulation with 1.5% carbopol was developed, exhibiting optimal viscosity (1245 cps) and a suitable pH (6.45) for topical use.